Quality of Life of Patients with Diabetes Mellitus Based on Their Characteristics - Joeliantina, Anita; Antasyia, Nur Lailia; Hamid, Irfany Nurul; Purnamawati, Dewi (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2023)
The quality of life of patients with diabetes mellitus (DM) describes the degree of health and limitations that need to be evaluated to administer treatment. The purpose of this study was to identify quality of life based on patient characteristics. This research is descriptive with a cross-sectional approach. The sample size used was 87 adult patients with DM determined through purposive sampling techniques. This research was carried out from December 2021 to January 2022 at the Bangkingan Surabaya Health Center. Data was collected using questionnaires and analyzed using descriptive analysis. The results of this study showed that patients with DM who had a high quality of life were 50.6% and 49.4% showed a low quality of life. Based on the identification of patient characteristics data that describe the high quality of life are early elderly patients with an age range of 46-55 years (25.3%), female (39.1%), high school education (18.4%), and not working (33.5%). Other data obtained were patients with no family history (31.1%), duration of DM 1-5 years (26.5 and the majority using a single antidiabetic drug. Based on these data, patients still need to get continuous education to manage diabetes. blood glucose levels and can improve quality of life. The characteristics of DM sufferers can be an alarm that makes sufferers aware of the changes that occur in them. Patients who can recognize the characteristics in themselves will be able to maintain their quality of life.